STRATEGI GREETER DALAM MENINGKATKAN PELAYANAN PRIMA UNTUK MEMINIMALISIR KOMPLAIN DI ABHAYAGIRI RESTAURANT YOGYAKARTA - Setyoatmodjo, Kukuh; Rusdiana, Restu Putri (JURNAL NUSANTARA, 2023)
Abhayagiri Restaurant is well known both in the city of Yogyakarta and outside the city of Yogyakarta, thus many guests come to Abhayagiri Restaurant. To support smooth operations, Abhayagiri Restaurant has its own standard procedures to improve excellent service to guests who come to the restaurant. At Abhayagiri Restaurant, which is usually a source of guest dissatisfaction, it is generally caused by less than optimal service from a greeter because the number of guests who come is not proportional to the number of existing waiter/waitress staff, so in this case the greeter cannot carry out all the sequence of service procedures, because the greeter also doubles as a waiter/waitress. The importance of the service of a greeter is to give the guest the first and last impression. If the guest is impressed with the service received, it will create a plus for the restaurant, which will make the guest come back again and increase guest visits. To achieve this, a greeter must know the strategy to improve excellent service. Therefore, the author raised the title "Greeter's Strategy In Improving Excellent Service To Minimize Complaints At Abhayagiri Restaurant Yogyakarta". The purpose of this study is to determine the greeter strategy in improving excellent service to minimizing complaints at Abhayagiri Restaurant. The method used is using descriptive qualitative research methods and data collection methods by observation and interviews. The results of the research are that there are still complaints because the greeter in carrying out the job desk has not been maximized, it can be seen that there are guest complaints that feel less attention or do not match the expectations of guests because the greeter does not run all the sequences of service, due to the lack of waiter/waitress and greeter staff who are present. charge, making all work not in accordance with their respective job desks, such as the greeter must double as a waiter/waitress, so that the duties and responsibilities of the greeter do not run completely. Thus there is a need for flexible waiter/waitress manning staff arrangements, so that the greeter does not double as a waiter/waitress, and the addition of people for the greeter section of at least two people in one shift so that the greeter can perform all stages of the sequence of service properly so that guests feel satisfied and well served. Greeter is still not optimal in establishing communication with related departments which causes miss communication with guests. So there are still guest complaints related to things that were not prepared according to the initial request. To minimize these omissions, it is necessary to improve communication with other departments and the greeter must be active and careful in recording guest requests.